Impact of Two Commercial Enzymes on the Release of Inositols, Fermentable Sugars, and Peptides in the Technology of Buckwheat Beer. (3rd April 2019) - Duliński, Robert; Zdaniewicz, Marek; Pater, Aneta; Żyła, Krzysztof
Abstract: The impact of two commercial enzyme preparations (Mats L Classic, Brewers Compass) used for mashing buckwheat malt was studied to assess their efficacies in releasing D- chiro- and myo -inositols, fermentable sugars and low molecular weight proteins and peptides. Concentrations of these compounds were determined in buckwheat malt, wort, and beer using sensitive ion-exchange and size exclusion chromatography techniques. These were preliminary studies whose general aim was to research the possibilities of functional beer production that could be dedicated for patients with coeliac disease. The application of enzyme preparations had no significant (Brewers Compass) or only little impact (Mats L Classic) on the recovery of D- chiro -inositol (DCI) and myo -inositol (MI) present in the buckwheat malt. In contrast to DCI, whose concentration in the buckwheat beer was 0.3 mg/mL, a minor fraction of MI (11–14.8%) was released into the beverage. In comparison to a barley beer, the oligosaccharide profile of the buckwheat beer was characterized by a relatively high proportion of residual sugars with a degree of polymerization above 5. SEC–HPLC chromatography showed significant changes within the polypeptide fractions after mashing and malting, with a marked increase in the proportion of low molecular weight peptides.